Crystal engineering a textbook - Desiraju, G. R. (Gautam R.); Vittal, Jagadese J.; Ramanan, Arunachalam (Singapore : World Scientific Publishing Co. Pte Ltd., 2011)
"This book is important because it is the first textbook in an area that has become very popular in recent times. There are around 250 research groups in crystal engineering worldwide today. The subject has been researched for around 40 years but there is still no textbook at the level of senior undergraduates and beginning PhD students. This book is expected to fill this gap. The writing style is simple, with an adequate number of exercises and problems, and the diagrams are easy to understand. This book consists major areas of the subject, including organic crystals and co-ordination polymers, and can easily form the basis of a 30 to 40 lecture course for senior undergraduates."--
Mode of access: World Wide Web.
System requirements: Adobe Acrobat Reader.
Title from web page (viewed December 21, 2018).
Includes bibliographical references and index.
Keywords: Crystallography -- Textbooks; Crystal growth; Molecular crystals; Electronic books